How to build your own simple, low-cost, seismic system. Issue 1 (1st December 2018) - Dean, Tim; Nguyen, Nghia; Kepic, Anton
Abstract : Acquiring seismic data has typically been an expensive pursuit due to the high price of the acquisition systems. Such systems are also typically not easily adaptable to suit different acquisition scenarios. In this paper we detail how you can build your own simple, low-cost ( 60/channel), seismic acquisition system. Data recorded using such systems is comparable to that obtained using a far more expensive commercial seismograph. Seismic sources are similarly expensive with the only low-cost option being a sledgehammer. In this paper we also describe how to manufacture a small vibroseis unit from easily available components at a cost of less than 3, 000. This unit has a wider, more controllable, bandwidth than an impact source and can be easily adapted to create a shear wave source for MASW surveys.